2018
DOI: 10.1007/s11356-018-1960-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compost tea containing phosphogypsum on potato plant growth and protection against Fusarium solani infection

Abstract: Three composts made of industrial wastes were prepared by mixing olive oil mill waste water (OMW), olive pomace, coffee grounds, and phosphogypsum (0, 10, and 30%). Potato plants (Solanum tuberosum) cultivated in a greenhouse were used to screen compost tea suppressive ability. All compost tea treatments inhibited Fusarium solani growth and improved plant growth and response to F. solani infection. The antagonistic effects of the different treatments were associated with a marked increase of the antioxidant en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Furthermore, they produce multiple mycotoxins that are harmful to humans [15]. Therefore, the mechanisms of protection against Fusarium invasion have been extensively studied both in model plants [16] and in crops such as potato [17,18], tomato [19], and cereals [20,21], and it was found that PR2-5, PR8, and PR11-13 are involved in plant responses to Fusarium infection [2,17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they produce multiple mycotoxins that are harmful to humans [15]. Therefore, the mechanisms of protection against Fusarium invasion have been extensively studied both in model plants [16] and in crops such as potato [17,18], tomato [19], and cereals [20,21], and it was found that PR2-5, PR8, and PR11-13 are involved in plant responses to Fusarium infection [2,17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It also increases soil fertility by supplying the nutrients it contains, followed by remediation of the heavy metal toxicity as the best engineering strategy for the plants to survive safely in contaminated soil. It improves the soil condition and makes the plants grow better than normal plants [ 15 , 16 ]. The decline in fresh and dry weights of the plants under Cd suggested less assimilation of C or decreased photosynthetic activity, which resulted from metal accumulation in roots.…”
Section: Resultsmentioning
confidence: 99%
“…Reports showed that compost tea suppressed plant diseases such as fusarium (Fusarium solani) on potatoes (Solanum tuberosum; Samet et al, 2018); and powdery mildew (Sphaerotheca pannosa) on rose (Rosa spp. ; Seddigh & Kian, 2018).…”
Section: Introductionmentioning
confidence: 99%